Clinical management of non-faecium non-faecalis vancomycin-resistant enterococci infection. Focus on Enterococcus gallinarum and Enterococcus casseliflavus/flavescens. Issue 4 (April 2018) - Monticelli, Jacopo; Knezevich, Anna; Luzzati, Roberto; Di Bella, Stefano
Abstract: Enterococcus gallinarum and Enterococcus casseliflavus/flavescens are enterococci intrinsically resistant to vancomycin belonging to the E. gallinarum group. They are responsible mainly for healthcare-associated infections, in particular bloodstream, urinary tract and surgical wound infections. Diseases due to these bacteria are significantly increasing worldwide, as they are prone to cause infection in patients with concurrent hepatobiliary or oncohematological disorders. Along with their distinguishing vancomycin resistance, due to a chromosomally-encoded VanC operon, their additional intrinsic resistance to many antibiotics other than glycopeptides limits the therapeutic choices. In addition, their intrinsic vancomycin resistance, unlike the vancomycin resistance of Enterococcus faecalis and Enterococcus faecium caused by transmissible plasmids, poses different infection control issues. We focused on the therapeutic and infection control issues of clinical syndromes caused by E. gallinarum and E. casseliflavus/flavescens . We propose therapeutic algorithms on bloodstream infections, endocarditis, central nervous system infections, endophthalmitis and urinary tract infections. The implementation of infection control measures in cases of E. gallinarum and E. casseliflavus/flavescens infection or colonization should be evaluated on a case-by-case basis, especially for epidemic outbreaks or for isolates supposed to harbor a potential transmissible vancomycin-resistance phenotype.